Perencanaan Berbasis Data dalam Meningkatkan Kualitas Layanan Pendidikan di SMP Al Furqon dan SMP Asy Syafaah Kabupaten Jember - Abd.Muthalib; Ahmad Rifa'i Abun; Rita Linda (Jurnal Bintang Pendidikan Indonesia, 2025)
Improving the quality of educational services is a crucial aspect in ensuring effective learning and equitable access for all students. However, many schools still face challenges in strategic planning due to the lack of systematic data utilization in decision-making. This study employs a qualitative method with a case study approach at SMP Al Furqon and SMP Asy Syafaah in Jember Regency, which implement Data-Based Planning (PBD) through the Identify, Reflect, and Improve (IRB) method. Data collection was carried out through interviews, observations, and document analysis related to the implementation of PBD in schools. The findings indicate that the implementation of PBD contributes to improving school management effectiveness, student academic achievement, and the satisfaction of educators and parents. Schools that apply PBD can allocate resources more efficiently based on measurable needs analysis. Additionally, schools with better data management systems tend to identify and address educational issues more quickly. This research contributes to strengthening data-driven education policies to enhance the quality of school services sustainably and provides a strategic implementation model for other schools seeking to adopt a similar approach.